Essential Health Care Services Addressing Intimate Partner Violence - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
A National Academies committee was tasked with identifying essential health care services for women related to intimate partner violence (IPV) during steady state conditions, determining whether the essential health care services related to IPV differ during public health emergencies (PHEs), and identifying strategies to sustain access to those essential health care services during PHEs. This report, Essential Health Care Services Addressing Intimate Partner Violence, presents findings from research and deliberations and lays out recommendations for leaders of health care systems, federal agencies, health care providers, emergency planners, and those involved in IPV research.
Keywords: Health and Medicine

Harassment and Violence Against Health Professionals Who Provide Reproductive Care: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
In December 2023, the National Academies hosted a public webinar in which medical and human rights experts explored concerns related to harassment, threats, and physical attacks against health care professionals working to provide essential reproductive health care. The event was the fourth in a webinar series designed to consider society-wide effects of limits to reproductive health care access in the U.S. following the 2022 Supreme Court Decision in Dobbs v. Jackson Womens Health Organization. This Proceedings of a Workshop-in Brief highlights the presentations and discussions that occurred at the webinar.
Keywords: Health and Medicine; Behavioral and Social Sciences

Community Safety as a Social Determinant of Health: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Roundtable on Population Health Improvement and the Forum on Mental Health and Substance Use Disorders held a public workshop in December 2023 to explore various dimensions of community safety and violence prevention in the U.S. Speakers highlighted attributes of physical spaces and social structures that create and reinforce safer communities. Discussions also covered identity-based violence, threats to interpersonal safety, frameworks for reimagining safety, and related policy and program solutions.
Keywords: Behavioral and Social Sciences; Health and Medicine

Identifying Military Resources and Strategies to Improve Civilian Airport Resiliency (The National Academies Press, 2024)
The U.S. military has established resilience practices for domestic installations, and a number of different military organizations, such as the Air National Guard, are co-located at civilian airports. This situation provides opportunities for airports to learn from military resilience practices. ACRP Synthesis 133: Identifying Military Resources and Strategies to Improve Civilian Airport Resiliency, from TRB's Airport Cooperative Research Program, documents resiliency practices and processes from the National Guard and other military services that airports can adapt and leverage for their own facilities and in partnerships with co-located military facilities.
Keywords: Transportation and Infrastructure

Reducing Intergenerational Poverty - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Experiencing poverty during childhood can lead to lasting harmful effects that compromise not only children’s health and welfare but can also hinder future opportunities for economic mobility, which may be passed on to future generations. This cycle of economic disadvantage weighs heavily not only on children and families experiencing poverty but also the nation, reducing overall economic output and placing increased burden on the educational, criminal justice, and health care systems. Reducing Intergenerational Poverty examines key drivers of long- term, intergenerational poverty, including the racial disparities and structural factors that contribute to this cycle. The report assesses existing research on the effects on intergenerational poverty of income assistance, education, health, and other intervention programs and identifies evidence-based programs and policies that have the potential to significantly reduce the effects of the key drivers of intergenerational poverty. The report also examines the disproportionate effect of disadvantage to different racial/ethnic groups. In addition, the report identifies high-priority gaps in the data and research needed to help develop effective policies for reducing intergenerational poverty in the United States.
Keywords: Behavioral and Social Sciences

Exploring the Power of Youth Leadership in Creating Conditions for Health and Equity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Young people often engage and lead efforts to improve the social, economic, and environmental factors that influence the health and equity of communities and the nation. The National Academies Roundtable on Population Health Improvement hosted a hybrid public workshop in September 2023 at The California Endowment Center for Healthy Communities in Oakland, California to discuss the power of youth leadership in creating conditions for health and equity and the civic infrastructure and resources that support youth participation and leadership in change efforts.
Keywords: Health and Medicine

Climate Security in Central America: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To advance a systems understanding of climate-related security risks in the Central America region, the National Academies of Sciences, Engineering, and Medicine convened a workshop titled Climate Security in Central America on May 3-4, 2023. The workshop was held under the auspices of the National Academies Climate Security Roundtable. Over two days, workshop participants considered some of the underlying environmental, social, economic, and political dynamics at play in Central America; they explored indicators and pathways for climate-related security risks in the region; and they considered the available tools for analyzing and forecasting these risks. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies; Conflict and Security Issues

Transit Exclusion Policies in Public Transportation Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Many operators of passenger public transportation maintain an exclusion or trespass policy that effectively bans violators from using the system for a period of time in conjunction with, or in lieu of, other penalties related to the violation. Exclusion policies vary in scope, qualifiers, purpose, and approach. TCRP Synthesis 173: Transit Exclusion Policies in Public Transportation Systems, from TRB's Transit Cooperative Research Program, documents the practice of the use of transportation exclusion policies in North American transit systems. It is designed to help transit agencies in understanding the usefulness of such policies, as well as understanding the methods for creating, amending, or supplementing exclusion policies to maximize their effectiveness in reducing crime and disorder within their respective transit systems.
Keywords: Transportation and Infrastructure

Data Integration in Learning Health Care Systems for Traumatic Brain Injury: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Traumatic brain injuries (TBI) affect millions of Americans each year, causing symptoms that can be debilitating and long-lasting and resulting in physical, cognitive, emotional, and financial ramifications. The complexity and heterogeneity of TBI make it challenging to target the right interventions to the right patient at the right time. For those who do receive care, unlinked health records, fragmented care delivery, and gaps in medical surveillance means many questions remain unanswered about TBI prevalence, comorbidities, adverse outcome risk factors, and long-term outcomes. To help address this challenge, learning health care systems that bidirectionally exchange data and insights across clinical research, care services, and public health have been identified as key to improving patient outcomes. To help move the field forward, the National Academies Forum on Traumatic Brain Injury hosted a public workshop to explore the role of learning health systems in advancing TBI research and care. This Proceedings of a Workshop summarizes discussions and key messages from the workshop.
Keywords: Health and Medicine

Homelessness: A Guide for Public Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Unemployment, low wages, poverty, and lack of affordable housing are the main drivers of an increasing homeless population throughout the U.S. in recent years. Transit agencies are being impacted by homelessness. While transit agencies cannot address the underlying causes of homelessness, there are opportunities to work with local partners to be a part of helping individuals in need, while providing a safe, reliable, and customer-friendly experience for all riders. TCRP Research Report 242: Homelessness: A Guide for Public Transportation, from TRB's Transit Cooperative Research Program, presents transit agency experiences and lessons learned as they have built on, newly implemented, or are considering programmatic activities that respond to homelessness.
Keywords: Transportation and Infrastructure

Roundtable on Population Health Improvement: Annual Report 2023 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The Roundtable on Population Health Improvement was established in February 2013 to bring together philanthropy, community-based organizations, health care delivery, governmental public health, academia, and business in a wide-ranging dialogue about what is needed to improve health in the United States and across diverse populations. In 2023, the roundtable hosted workshops, webinars, and other activities that continued its exploration of the social drivers of health of past and persisting racially unjust systems and structures that shape those drivers.
Keywords: Health and Medicine

Social Media and Adolescent Health - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Social media has been fully integrated into the lives of most adolescents in the U.S., raising concerns among parents, physicians, public health officials, and others about its effect on mental and physical health. Over the past year, an ad hoc committee of the National Academies of Sciences, Engineering, and Medicine examined the research and produced this detailed report exploring that effect and laying out recommendations for policymakers, regulators, industry, and others in an effort to maximize the good and minimize the bad. Focus areas include platform design, transparency and accountability, digital media literacy among young people and adults, online harassment, and supporting researchers.
Keywords: Health and Medicine

Valuing America's Health: Aligning Financing to Reward Better Health and Well-Being - National Academy of Medicine (The National Academies Press, 2024)
The United States is experiencing a decline in life expectancy despite high health care spending due to a multitude of factors, including the COVID-19 pandemic, opioid epidemic, high burden of chronic disease, and systemic and structural inequities.A response proportional to this crisis is required. Valuing America's Health: Aligning Financing to Reward Better Health and Well-Being explores opportunities to transform the current health and health care system to one that promotes whole person and whole population health. The publication emphasizes the need for a bold vision and sustainable financing strategies to prioritize health and well-being for all. Authors of the publication highlight the importance of building a movement to prioritize health, repairing systemic failures, holding stakeholders accountable, controlling health care costs, incentivizing health promotion, adopting collaborative financing and policy-making approaches, and empowering individuals and communities in health decision-making.The way is clear; what is needed now is the will to move forward. Learn more about how to ensure our nation's health and health care system can support optimal health for all.
Keywords: Health and Medicine

The Science of Engaging Youth Lived Experience in Health Research, Practice, and Policy: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
There is a growing body of evidence demonstrating the value of incorporating youth voices in the development of research and programming aimed at supporting youth well-being. On October 11 and 12, 2023, the Forum for Childrens Well-Being hosted a two-day virtual public workshop, The Science of Engaging Youth Lived Experience in Health Research, Practice, and Policy, which was designed to explore the impacts of youth participatory methods including the potential for participatory methods to produce more effective, relevant, and sustainable interventions; the potential for participatory methods to engage historically marginalized communities among youth; the challenges of instituting participatory methods, including time, budgetary expenditures, and training; and opportunities to better incorporate participatory methods into research, systems, and programs for child well-being.
Keywords: Behavioral and Social Sciences

Facial Recognition Technology: Current Capabilities, Future Prospects, and Governance - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Facial recognition technology is increasingly used for identity verification and identification, from aiding law enforcement investigations to identifying potential security threats at large venues. However, advances in this technology have outpaced laws and regulations, raising significant concerns related to equity, privacy, and civil liberties. This report explores the current capabilities, future possibilities, and necessary governance for facial recognition technology. Facial Recognition Technology discusses legal, societal, and ethical implications of the technology, and recommends ways that federal agencies and others developing and deploying the technology can mitigate potential harms and enact more comprehensive safeguards.
Keywords: Computers and Information Technology; Behavioral and Social Sciences; Engineering and Technology

Harm Reduction Services for People Who Use Drugs: Exploring Data Collection, Evidence Gaps, and Research: Proceedings of a Workshop–in Brief - National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Given the public health emergency posed by drug overdoses, there have been calls for a comprehensive approach to drug policy that would include focusing on reducing harm for people who use drugs. To explore data collection efforts, evidence gaps, and research needs for harm reduction, the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop on January 30-31, 2024, sponsored by the Office of National Drug Control Policy, Executive Office of the President. The workshop focused on harm reduction strategies and services that aim to prevent overdose and infectious disease transmission; enhance the health, safety, and well-being of people who use drugs; and offer low-threshold options for accessing substance use disorder treatment. This Proceedings of a Workshop-in Brief summarizes the presentations and discussions that occurred at the workshop.
Keywords: Health and Medicine

Creating an Integrated System of Data and Statistics on Household Income, Consumption, and Wealth: Time to Build - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Many federal agencies provide data and statistics on inequality and related aspects of household income, consumption, and wealth (ICW). However, because the information provided by these agencies is often produced using different concepts, underlying data, and methods, the resulting estimates of poverty, inequality, mean and median household income, consumption, and wealth, as well as other statistics, do not always tell a consistent or easily interpretable story. Measures also differ in their accuracy, timeliness, and relevance so that it is difficult to address such questions as the effects of the Great Recession on household finances or of the Covid-19 pandemic and the ensuing relief efforts on household income and consumption. The presence of multiple, sometimes conflicting statistics at best muddies the waters of policy debates and, at worst, enable advocates with different policy perspectives to cherry-pick their preferred set of estimates. Achieving an integrated system of relevant, high-quality, and transparent household ICW data and statistics should go far to reduce disagreement about who has how much, and from what sources. Further, such data are essential to advance research on economic wellbeing and to ensure that policies are well targeted to achieve societal goals. Creating an Integrated System of Data and Statistics on Household Income, Consumption, and Wealth reviews the major household ICW statistics currently produced by U.S. statistical agencies and provides guidance for modernizing the information to better inform policy and research, such as understanding trends in inequality and mobility. This report provides recommendations for developing an improved 21st century data system for measuring the extent to which economic prosperity is shared by households throughout the population and for understanding how the distribution of resources is affected by government policy and economic events.
Keywords: Behavioral and Social Sciences

Community-Driven Relocation: Recommendations for the U.S. Gulf Coast Region and Beyond - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Between 1980 and mid-2023, 232 billion-dollar disasters occurred in the U.S. Gulf Coast region, with the number of disasters doubling annually since 2018. The variety and frequency of storms have exacerbated historic inequalities and led to cycles of displacement and chronic stress for communities across the region. While disaster displacement is not a new phenomenon, the rapid escalation of climate-related disasters in the Gulf increases the urgency to develop pre-disaster policies to mitigate displacement and decrease suffering. Yet, neither the region nor the nation has a consistent and inclusionary process to address risks, raise awareness, or explore options for relocating communities away from environmental risks while seeking out and honoring their values and priorities. Community-Driven Relocation: Recommendations for the U.S. Gulf Coast Region and Beyond examines how people and infrastructure relocate and why community input should drive the planning process. This report provides recommendations to guide a path for federal, state, and local policies and programs to improve on and expand existing systems to better serve those most likely to be displaced by climate change.
Keywords: Behavioral and Social Sciences

Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K–12, undergraduate, and graduate and professional levels.
Keywords: Education

Addressing the Rising Mental Health Needs of an Aging Population: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Existing systems are not prepared to provide the mental health care services needed by the growing population of older adults. The National Academies Forum on Mental Health and Substance Use Disorders hosted a public workshop in May 2023 to highlight the current state of mental health care for older adults, outline the challenges they face, and explore potential long-term strategies and solutions for addressing unmet mental health needs. Discussions emphasized information about wellness and prevention, social determinants of health in aging populations, the impact of workforce shortages and gaps, the need for supportive healthy communities, and strategies to promote positive mental health.This publication summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine